Circular No. 19 of the year 2025 On Giving the Employees Addressed by the Provisions of the Labour Law Promulgated by law No. 14 of the year 2025 an Official Paid Holiday on the Occasion of the Anniversary of 6th of October Victory (the Armed Forces Day) - Ministry of Manpower (بوابة مصر للتحول الرقمي, 2025)
In implementation of the provision of article (129) of the Labour Law No. 14 of the year 2025, private sector employees are entitled to a paid leave on the holidays and occasions, as determined by a decree issued by the minister concerned with labour affairs. Whereas the first paragraph of article-11 of the enactment articles of labour law no. 14 of the year 2025 stipulates that “the minister concerned with labour affairs shall issue the decrees enforcing the provisions of this law and the attached law within a period not exceeding ninety days as of the date of enforcement thereof. Until these decrees are issued, the decrees applicable in this regard shall remain in effect, provided that they do not contradict the provisions of this law and the attached law”, and In light of the issuance of Prime Minister’s Decree No. (3445) of the year 2025, stipulating that Thursday, October 9th, 2025 (AD) shall be an official paid holiday on the occasion of the Anniversary of 6th of October Victory (the Armed Forces Day), instead of Monday, October 6th, 2025 (AD), for employees at ministries, government departments, public authorities, local administration units, public sector companies, and public business sector companies, and Out of the keenness to unify official holiday dates for all employees across various sectors of the State, whenever possible, in order to achieve the social and national objectives of official holidays on anniversaries and occasions, Therefore, it has been decided to give the employees addressed by the provisions of the Labor Law promulgated by Law No. 14 of the year 2025, a paid holiday on Thursday, October 9th, 2025, instead of Monday, October 6th, 2025, on the occasion of the Anniversary of 6th of October Victory (the Armed Forces Day). The employer may require the employee to work on that day if work conditions so necessitate, in which case the employee shall be entitled to double his wage in addition to his regular wage for that day, and provided that the employee shall be given another day off instead of that day, based on a written request by the employee to be lodged in his file. Accordingly, heads of central departments at the Ministry’s headquarters, as well as directors of labor directorates- each as far as he is concerned, are required to disseminate the provisions of this circular at workplaces and production sites, and to instruct that the provisions thereof should be put into effect. Issued on: 5/10/2025